(3JaSjQ GdbQBf GdcQjes
(3ChdgG (B:s
(3jHOA HCKfGA ChGFd ShQI GdReQ , Hbhdg (B" (3hCfRd dce (B" (3LYd hCfTG hCMOK , hYHQ HGdEfRGd dCfg bVGg hbSeg s
(3BNQgG (B:s
(3jfJgi CKfGA GhGFd ShQI GdLGKjI , Hbhdg (B: (3heG jHK cef OGHI (B" (3eYWha Ydi Ndbce aEf bdJ de LYdJg eYWha Ydi GdNdb deVGa hde JLYdg eYWhakG Ydi GdVejQ GdeVGa Edjg s
(3GdeDda djS GdbQWHi hdG CHG MjGf GdeDda jfbd Yf GHf YWjI cKjQkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs